Linear Systems (Three Variables) Test

About Solving Linear Systems in Three Variables:

To solve a linear system in three variables, we can use an extension of the elimination method. We begin by eliminating one of the variables from any two equations. We then eliminate the same variable in any other two equations. This creates a linear system in two variables. We solve this system and use substitution to find the third unknown.

Test Objectives:•Demonstrate the ability to eliminate one of the variables from a three variable linear system

•Demonstrate the ability to solve a linear system in two variables

•Demonstrate the ability to solve a linear system in three variables

Solving Systems of Linear Equations in Three Variables Test:

#1:

Instructions: Solve each linear system.

a) $$-5y - 7z = -9$$ $$x - y + 4z = 5$$ $$-x + 3y + 3z = 7$$

Watch the Step by Step Video Solution|

View the Written Solution#2:

Instructions: Solve each linear system.

a) $$-4x + 2y + z = 11$$ $$-3x + 5y + 6z = -4$$ $$-2x + 4y - z = 25$$

Watch the Step by Step Video Solution|

View the Written Solution#3:

Instructions: Solve each linear system.

a) $$5x - y + z = 22$$ $$-4x - 4y + 4z = 20$$ $$-4x - 3y + 3z = -13$$

Watch the Step by Step Video Solution|

View the Written Solution#4:

Instructions: Solve each linear system.

a) $$5x + y + 4z = -7$$ $$x + 7y - 6z = -15$$ $$-7x - 6y - z = 19$$

Watch the Step by Step Video Solution|

View the Written Solution#5:

Instructions: Solve each linear system.

a) $$6x + 6y - 10z = 17$$ $$6x + 21y + 3z = 28$$ $$30x - 12y - 12z = 17$$

Watch the Step by Step Video Solution|

View the Written SolutionWritten Solutions:

Solution:

a) {(-4,-1,2)} : x = -4, y = -1, z = 2

Watch the Step by Step Video Solution

Solution:

a) {(-2,4,-5)} : x = -2, y = 4, z = -5

Watch the Step by Step Video Solution

Solution:

a) No solution : ∅

Watch the Step by Step Video Solution

Solution:

a) {(-∞,∞)} : infinite number of solutions

Watch the Step by Step Video Solution

Solution:

a) $$\left\{\left(\frac{5}{6},\frac{7}{6},-\frac{1}{2}\right) \right\} : x = \frac{5}{6}, y = \frac{7}{6}, z = -\frac{1}{2}$$

Watch the Step by Step Video SolutionCopyright © 2016 GreeneMath.com